Hubungan Basic Psychological Needs dengan Student Engagement dalam Belajar - Shally Ardhina; Endang Supraptiningsih (UNISBA Press, 2022)
Abstract. High academic demands during high school are aimed at enabling students to achieve good academic achievements to continue their education to the next level. Student Engagement is important to gain knowledge and skills provided by the school. Phenomena in students of SMA Alfa Centauri class XI describe student involvement in class such as your presence, attention, asking questions, and showing positive reactions during the learning process, but the researchers also found that some students did their own activities, such as being late at school, not paying attention to the teacher when teaching, is not active in the learning process and does not understand the material, causing his academic achievement to decline. The lack of student involvement is due to several factors, one of which is basic psychological needs. The purpose of this study is to obtain empirical data on how closely the relationship between Basic Psychological Needs and Student Engagement of class XI students of SMA Alfa Centauri Bandung is. The research data was obtained from the Student Engagement theory measuring instrument (Fredricks et al., 2004) which was distributed to 151 class XI students of SMA Alfa Centauri. This research uses correlational quantitative method and uses simple random sampling technique. Data analysis using Spearman rank correlation test. The results showed that there was a positive correlation between Basic Psychological Needs and Student Engagement with a correlation coefficient of 0.665. This means that the higher the Basic Psychological Needs, the higher the Student Engagement. Abstrak. Tuntutan akademik yang tinggi pada masa SMA bertujuan agar siswa mampu mencapai prestasi akademik yang baik untuk melanjutkan jenjang pendidikan selanjutnya. Student Engagement adalah hal yang penting untuk mendapatkan ilmu pengetahuan dan keterampilan yang diberikan oleh sekolah. Fenomena pada siswa SMA Alfa Centauri kelas XI menggambarkan student engagement di kelas seperti kehadiran, perhatian, bertanya, dan menunjukkan reaksi positif pada saat proses pembelajaran, namun peneliti menemukan juga sebagian siswa melakukan kegiatannya sendiri, seperti terlambat hadir sekolah, tidak memperhatikan guru saat mengajar, tidak aktif dalam proses pembelajaran dan tidak memahami materi sehingga menyebabkan prestasi akademiknya menurun. Kurangnya engagement siswa dikarenakan beberapa faktor salah satunya adalah basic psychological needs. Tujuan dari penelitian ini memperoleh data empiris mengenai seberapa erat hubungan Basic Psychological Needs dengan Student Engagement siswa kelas XI SMA Alfa Centauri Bandung. Data penelitian diperoleh dari alat ukur teori Student Engagement (Fredricks et al., 2004) yang disebarkan kepada 151 siswa kelas XI SMA Alfa Centauri. Penelitian ini menggunakan metode kuantitatif korelasional dan menggunakan teknik simple random sampling. Data analisis menggunakan uji korelasi rank spearman. Hasil penelitian menunjukkan bahwa terdapat korelasi positif antara Basic Psychological Needs dengan Student Engagement dengan nilai koefisien korelasi sebesar 0,665. Artinya semakin tinggi Basic Psychological Needs maka semakin tinggi pula Student Engagement.